ELAP NEEDS ANALYSIS FOR LAW STUDENTS - Jalil, Nur Muhammad Insan; Kamarudin, Mohd Fauzi (Journal of Human Capital Development (JHCD), 2009)
Malaysia is a unique country. Although Bahasa Malaysia is the national language, English language is still widely used in various situations. This flexibility has resulted to the use of English language in the legal profession in matters such as law-making processes, judicial proceedings, court proceedings and legal service (Noraini Ibrahim, 1997:19). Thus, it is imperative that law practitioners are proficient in the language to be effective in their profession. They should be equipped with the necessary language skills and sub-skills from their undergraduate years to enable them to cope well with the complex legal language used in legal textbooks, research journals, case books, law reports and Acts. This study looks into the language needs of law students in the International Islamic University Malaysia. The sample for the study consisted of law students and law subject lecturers. Two types of questionnaires were used in this study: students’ questionnaire and lecturers’ questionnaire. The findings of the study are discussed and implications of it towards the teaching of ESP for Law students are presented for future researchers. Keywords: needs analysis, language proficiency, English for law